A Systematic Literature Review: Chitosan-Based Membrane for Pollutant Removal from Wastewater - Muhammad Nur Alam (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
This review synthesizes research on development of synthesis techniques and modification methods for chitosan- based membranes, all application areas for pollutant separation to address inconsistencies in membrane performance and limited comparative analyses across pollutant classes. The review aimed to evaluate synthesis and chemical modification strategies, benchmark fabrication methods for mechanical strength and selectivity, identify nanomaterial integration approaches, compare pollutant removal efficiencies, and analyze challenges in membrane applications. A systematic analysis of studies from diverse synthesis methods—including phase inversion, electrospinning, and 3D printing—and modification approaches such as chemical crosslinking and nanomaterial incorporation was conducted. Findings reveal that nanocomposite and crosslinked membranes exhibit enhanced mechanical stability, permeability, and selective removal of heavy metals, dyes, and organic pollutants, with adsorption capacities reaching up to 1500 mg/g and oil-water separation efficiencies exceeding 98%. However, variability in synthesis protocols, limited regeneration data, and insufficient real wastewater evaluations constrain practical scalability. Integration of photocatalytic and antifouling modifications improves fouling resistance and operational longevity, though long-term durability remains underexplored. These results underscore the potential of tailored chitosan-based membranes for multifunctional pollutant separation while highlighting the need for standardized methodologies and comprehensive regeneration studies. The synthesis informs future research directions to optimize membrane design and facilitate broader implementation in sustainable water treatment technologies.